Anatomical variations in coronary venous drainage: challenges and solutions in delivering cardiac resynchronisation therapy. (19th May 2022) - Akhtar, Z; Sohal, M; Kontogiannis, C; Leung, LWM; Harding, I; Zuberi, Z; Bajpai, A; Norman, M; Pearse, S; Beeton, I; Gallagher, MM
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Cardiac resynchronisation therapy (CRT) is the cornerstone of heart failure management. Delivery of a left ventricular lead can occur in a small proportion of patients undermining the benefits of this treatment. Abnormal coronary venous anatomy is a contributing factor to this failure. Although epicardial lead placement is available, this patient cohort requiring CRT is subject to higher peri-operative morbidity and mortality than the general population; a transvenous approach is preferable. Purpose: To investigate the abnormalities of the coronary venous system in candidates for cardiac resynchronization therapy (CRT) and describe methods for circumventing the resulting difficulties. Methods: From 4 implanting institutes, data of all CRT implants between October 2008-October 2020 were screened for abnormal cardiac venous anatomy, defined as an anatomical variation not conforming to the accepted 'normal' anatomy. Patient demographics, procedural detail and subsequent left ventricle (LV) lead pacing indices were collected. Results: From a total of 3548 CRT implants, 15 (0.42%) patients (80% male) of 72.2±10.6 years in age with a LV ejection fraction of 34±10.3% were identified to have had an abnormal cardiac venous anatomy over the study period. There were 13 cases of persistent left side superior vena cava (pLSVC), 5 of which had coronary sinus ostium atresia (CSOA) including 2 with an 'unroofed' coronary sinus (CS); 1 patient had a unique anomalous origin of the CS and 1 patient had an isolated CSOA. In total 14 patients (60% repeat attempt) had successful percutaneous implant under general anaesthesia (46.7%) via the cephalic vein (59.1%), using the femoral approach (53.3%) for levophase venography and/or pull-through, including 1 case of endocardial LV implant. Pacing follow-up over 37.64±37.6 months demonstrated LV lead threshold between 0.62-2.9 volts (pulsewidth 0.4-1.5 milliseconds) in all cases; 5 patients died within 2.92±1.6 years of successful implant. Conclusion: CRT devices can be implanted percutaneously even in the presence of substantial abnormalities of coronary venous anatomy. Alternative routes of venous access may be required.